ESTIMASI NILAI PASAR WAJAR SAHAM PT INDOFARMA TBK. DALAM RANGKA AKUISISI OLEH PT KIMIA FARMA TBK. TAHUN 2012 - , Suharsono; , Dr. Mamduh M. Hanafi, M.B.A., ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aims to estimate the fair market value of PT Indofarma shares in 2012, associated with the plan of PT Kimia Farma to acquire of some shares of PT Indofarma. The fair market value of PT Indofarma shares obtained by using several methods can be used as a reference for determining the value of the acquisition. This research is important because if not done correctly in calculation, the price obtained during the acquisition would be much different from fair value. Data source consists of PT Indofarma Financial statement for the last six financial statements and other information contained in the annual report of PT Indofarma for period 2005 to 20010, financial statement in 2011 (quarter III) of PT Indofarma, financial statements in 2010 and 2011 (quarter III) of the comparable companies, PT Indofarmaâs stock price, the comparable companies's stock price